Latest Insights in Alcohol-Related Liver Disease and Alcoholic Hepatitis - Enciu Vlad-Teodor; Ologeanu Priscila Mădălina; Constantinescu Alexandru; Fierbinteanu-Braticevici Carmen (Romanian Journal of Internal Medicine)
Alcohol-related liver disease (ALD) is still to this date one of the leading causes of chronic liver disease globally. ALD comprises a wide disease spectrum, from the benign liver steatosis, to the life-threatening inflammatory acute phenotype of alcoholic hepatitis (AH) and ultimately, advanced liver fibrosis and cirrhosis. AH represents an acute inflammatory liver condition caused by prolonged high quantities of alcohol intake. Disease outcome varies from mild to severe, with systemic implication and high mortality. Although the pathogenesis has been extensively studied over the years, little progress has been made regarding therapeutic options. In over 50 years, steroid treatment is still the cornerstone therapeutic option, albeit having multiple limitations and a low success rate. On the other hand, important progress has been made regarding disease management and severity stratification with the implementation of different prognostic score. Although highly prevalent, AH still has many unmet needs, with a growing necessity for novel non-invasive diagnosis, prognosis biomarkers and impactful treatment options.